Comparison of the Effectiveness of Shame-Awareness Therapy and Cognitive-Behavioral Therapy on Self-Regulation Behaviors and Psychological Symptoms in Adolescent Girls with Gender Dysphoria - Baharvand, Mahin; Araban, Shoja; kordestani, Davoud (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The study aimed to compare the effectiveness of stress-based mindfulness training and acceptance and commitment therapy (ACT) on reducing social anxiety and increasing perfectionism among female high school students.Methods and Materials: This experimental study employed a pre-test, post-test, and one-month follow-up design with a control group. The sample consisted of 45 female high school students from District 4 of Tehran, selected using convenience sampling and randomly assigned to two experimental groups and one control group (15 participants per group). The Social Phobia Inventory (SPI) by Connor et al. (2000) and the Positive and Negative Perfectionism Questionnaire by Terry-Short et al. (1995) were used to measure the dependent variables—social anxiety and perfectionism—before and after the intervention. The interventions consisted of eight sessions of stress-based mindfulness training and ACT. Covariance analysis (ANCOVA) was used to analyze the data.Findings: The ANCOVA results indicated a significant difference between the experimental and control groups regarding social anxiety reduction (F(1,27) = 95.365, p < .001) and an increase in perfectionism (F(1,26) = 98.719, p < .001) after controlling for pre-test scores. The findings confirmed that both stress-based mindfulness training and ACT effectively reduced social anxiety and increased perfectionism, with significant differences observed between the two interventions and the control group.Conclusion: The study concluded that both stress-based mindfulness training and ACT are effective interventions for reducing social anxiety and increasing perfectionism in female high school students. The results suggest that these interventions can be valuable tools in educational and therapeutic settings to enhance students' psychological resilience and well-being. The findings also highlight the importance of incorporating these approaches into the curriculum of psychology and counseling programs to better prepare future professionals in managing anxiety and perfectionism.